Evaluation of the Proliferation and Invasion of Human Hepatocellular Carcinoma Cells Subjected to Epirubicin Formulated with Natural Oils in Nanoemulsion - Alkhatib, Mayson H. (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Nanoformulation provides a promising potential for drug delivery of the chemotherapeutic agents. The current study aimed to solubilize the anticancer drug, epirubicin (EPI), in nanoemulsion consisting of algae (AGA) and cinnamon (CNAM) oils and to evaluate the antitumor activity of the new formula (EPI-AGA-CNAM) on the HepG2 and Huh7 hepatocellular carcinoma (HCC) cells. Materials and Methods: The size, surface charge, drug release, anticancer potential, flow cytometric analyses of apoptosis, reactive oxygen species (ROS) generation, and anti-invasion ability were investigated for the new nanoformulations. Results: The nanodroplets of EPI-AGA-CNAM, analyzed by the dynamic light scattering, were homogeneously distributed with a mean Z-average diameter and zeta potential of 109.90 ± 2.97 nm and −2.98 ± 0.22, respectively. The enhanced cytotoxicity and apoptotic effect of EPI-AGA-CNAM were observed in HepG2 and Huh7 cell lines as compared to free EPI (P < 0.001). The higher amounts of ROS formation in the HCC cells were indicated by the increased sensitivities of the fluorescence DCFH-DA probe in EPI-AGA-CNAM-treated HepG2 and Huh7 cells of 84.56 ± 2.21 and 78.01 ± 3.30, respectively, when compared to those of free EPI-treated cells of 13.6 ± 3.77 and 11.67 ± 4.28, respectively. EPI-AGA-CNAM treatment reduced the invasion ability in both cell lines by about 39%, whereas EPI treatment reduced the invasion ability of HepG2 and Huh7 to 55.58% and 63.35%, respectively. Conclusion: EPI-AGA-CNAM-induced apoptosis in HCC cell lines through ROS generation and the inhibition of the invasion ability.